A frog antioxidant peptide protects against myocardial ischemia reperfusion injury in rats. Issue 1 (1st January 2020) - Lin, Zhi; Jiang, Yongliang; Yang, Ping; Sun, Lin; Lu, Di
Abstract : Excessive reactive oxygen species (ROS) induced by myocardial ischemia reperfusion (IR) injury exert detrimental effects on cardiomyocytes. Antioxidant peptides can scavenge free radicals such as 2, 2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS + ), 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and nitic oxide (NO) in vitro, but little is known about their functions in vivo . Here, we evaluated the effects of an antioxidant peptide (antioxidant-RL) used at the beginning of reperfusion on myocardial IR injury. We performed 2, 3, 5-triphenyltetrazolium chloride staining (TTC) to determine myocardial infarct size. Creatine kinase isoenzyme-MB (CK-MB), cardiac troponin-T (CTnT), tumor necrosis factor-alpha (TNF-α), and interleukin-6 (IL-6) levels were determined with enzyme-linked immunosorbent assays (ELISAs). The levels of ROS were measured with a fluorometric Intracellular ROS kit. The expression levels of apoptosis-related proteins in cardiomyocytes were detected by western blotting. Antioxidant-RL (10 mg/kg) reduced the infarct size and levels of CK-MB and CTnT in rats. The levels of TNF-α and IL-6 also decreased. Furthermore, ROS levels were ameliorated and the expression of apoptosis-related proteins in myocytes was down-regulated by antioxidant-RL (100 µg/mL). Antioxidant-RL exerted protective effects on myocardial IR injury by scavenging excessive ROS, suppressing inflammatory factors, and inhibiting cardiomyocytes apoptosis. Thus, antioxidant-RL may serve as a potent candidate for the treatment of IR injury. GRAPHICAL ABSTRACT: